2013
DOI: 10.1176/appi.ps.201200235
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing Community: Perspectives of Individuals Diagnosed as Having Serious Mental Illness

Abstract: Objective Community integration is recognized as a crucial component of recovery from serious mental illness. Although the construct of community integration can be measured with structured instruments, little is known about the subjective and experiential meaning of community and community involvement for persons with serious mental illness. Methods In 2010, 30 individuals with serious mental illness treated in two public mental health clinics completed semistructured interviews that elicited the places and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 47 publications
5
59
0
1
Order By: Relevance
“…The women in this study living with “illness of the brain” experienced stigma. This is in keeping with findings of previous studies (Armour, Peterson, & Roseborough, ; Bromley et al, ; Manuel et al, ; Mezey et al, ; NHS Health Scotland, ). Sources of stigma for the women in this study arose from self, professionals, family members and society (Jenkins et al, ; NHS Health Scotland, ).…”
Section: Discussionsupporting
confidence: 92%
“…The women in this study living with “illness of the brain” experienced stigma. This is in keeping with findings of previous studies (Armour, Peterson, & Roseborough, ; Bromley et al, ; Manuel et al, ; Mezey et al, ; NHS Health Scotland, ). Sources of stigma for the women in this study arose from self, professionals, family members and society (Jenkins et al, ; NHS Health Scotland, ).…”
Section: Discussionsupporting
confidence: 92%
“…In the remodelled welfare states of the twenty‐first century politicians and policy makers expect people to take care of themselves and each other (Hurenkamp & Tonkens, 2011; Tonkens, ; Tonkens & De Wilde, 2013). People with psychiatric and intellectual disabilities should be taken care of by family and friends, but also by neighbours, colleagues and others who meet disabled people in their social lives (Bromley et al, ; Yanos, Stefancic, & Tsemberis, ). In this article we focus on the relationship between people with psychiatric and intellectual disabilities and other citizens not being professional carers or family members.…”
Section: Introduction: the Caring Societymentioning
confidence: 99%
“…Recovery from mental illness is a complex process that includes adaptation to the diagnosis, developing agency and a sense of self-determination, community integration, as well as optimism about recovery and treatment options (Green, 2004; Liberman & Kopelowicz, 2005; Bromley et al, 2013; Leamy, Bird, Le, Williams, & Slade, 2011). Clinical approaches to trauma treatment or treatment of post-traumatic stress disorder (PTSD) (Frueh et al, 2009; Mueser et al, 2008) have been evaluated among people with serious mental illnesses, but we found no studies of relationships between adverse events and measures of recovery.…”
Section: Introductionmentioning
confidence: 99%